Key management ratios : the 100+ ratios every manager needs to know - Walsh, Ciaran (Harlow, England ; New York : Prentice Hall/Financial Times, 2008)
This edition examines the subject of the integrity of accounting statements, discusses when and how integrity may be breached and suggests methods of detection.
Includes bibliographical references and index.
osa 17/05/13
Loans
Keywords: Ratio analysis; Management - statistical methods; Statistical decision